Diagnosis Of Endothelial Dysfunction In Children With Neurocirculatory Dystonia: Test With Reactive Hyperemia (Texas Journal of Medical Science, 2024)
The article examines the role of nitric oxide in the regulation of peripheral vascular tone in children with neurocirculatory dystonia. When using a functional test with reactive hyperemia, its high diagnostic significance was revealed; a decrease in the formation of nitric oxide in the vascular endothelium (endothelial dysfunction) was established in children with neurocirculatory dystonia (p